Non‐antibacterial tetracycline formulations: host‐modulators in the treatment of periodontitis and relevant systemic diseases. (23rd March 2016) - Golub, Lorne M.; Elburki, Muna S.; Walker, Clay; Ryan, Maria; Sorsa, Timo; Tenenbaum, Howard; Goldberg, Michael; Wolff, Mark; Gu, Ying
Abstract : Traditionally, the dental profession has primarily treated periodontitis using a mechanical/surgical, rather than a pharmaceutical, approach. However, based on experiments several decades ago which demonstrated that tetracyclines, unexpectedly, inhibit collagen‐ and bone‐destructive mammalian‐derived enzymes (e.g. the collagenases), and through non‐antibiotic mechanisms, the concept of host‐modulation therapy (HMT) was developed. Accordingly, two drug‐development strategies evolved: (i) the development of non‐antimicrobial formulations of doxycycline; and (ii) the chemical modification of tetracyclines to eliminate their antibiotic activity but retain (or even enhance) their anti‐collagenase properties. Regarding the latter, these chemically modified tetracyclines (CMTs) showed efficacy in vitro, in animal models of periodontal (and relevant systemic) disease, and in preliminary clinical trials on patients with Kaposi's sarcoma (however, at the high doses used, photosensitivity was a significant side‐effect). In the first strategy, subantimicrobial‐dose doxycycline (SDD) demonstrated safety and efficacy in human clinical trials and was approved by the U S Food and Drug Administration (U S FDA) and in other countries for the treatment of periodontitis (20 mg, twice daily, i.e. once every 12 hours) adjunctive to scaling and root planing, and for chronic inflammatory skin diseases (40‐mg sustained‐release 'beads'). SDD also showed efficacy in patients with systemic diseases relevant to periodontitis, including diabetes mellitus and arthritis, and in postmenopausal women with local and systemic bone loss. Importantly, long‐term administration of SDD, of up to 2 years, in clinical trials did not produce antibiotic side‐effects. SDD (and in the future, new HMTs, such as low‐dose CMT‐3, resolvins and chemically modified curcumins) may shift the paradigm of periodontal therapy from a predominantly surgical approach to the greater use of medicinal/pharmacologic strategies, ultimately to benefit larger numbers of patients.